Potency of several oximes to reactivate human acetylcholinesterase and butyrylcholinesterase inhibited by paraoxon in vitro - Jun, Daniel; Musilová, Lucie; Kuča, Kamil; Kassa, Jiří; Bajgar, Jiří (Chemico-biological interactions, 2008)
Organophosphorus pesticides (e.g. chlorpyrifos, malathion, and parathion) and nerve agents (sarin, tabun, and VX) are highly toxic organophosphorus compounds with strong inhibition potency against two key enzymes in the human body-acetylcholinesterase (AChE; EC 3.1.1.7) and butyrylcholinesterase (BuChE; EC 3.1.1.8). Subsequent accumulation of acetylcholine at synaptic clefts can result in cholinergic crisis and possible death of intoxicated organism. For the recovery of inhibited AChE, derivatives from the group of pyridinium or bispyridinium aldoximes (called oximes) are used. Their efficacy depends on their chemical structure and also type of organophosphorus inhibitor. In this study, we have tested potency of selected cholinesterase reactivators (pralidoxime, obidoxime, trimedoxime, methoxime and H-oxime HI-6) to reactivate human erythrocyte AChE and human plasma BuChE inhibited by pesticide paraoxon. For this purpose, modified Ellman's method was used and two different concentrations of oximes (10 and 100 microM), attainable in the plasma within antidotal treatment of pesticide intoxication were tested. Results demonstrated that obidoxime (96.8%) and trimedoxime (86%) only reached sufficient reactivation efficacy in case of paraoxon-inhibited AChE. Other oximes evaluated did not surpassed more than 25% of reactivation. In the case of BuChE reactivation, none of tested oximes surpassed 12.5% of reactivation. The highest reactivation efficacy was achieved for trimedoxime (12.4%) at the concentration 100 microM. From the data obtained, it is clear that only two from currently available oximes (obidoxime and trimedoxime) are good reactivators of paraoxon-inhibited AChE. In the case of BuChE, none of these reactivators could be used for its reactivation.
Keywords: financování organizované; Butyrylcholinesterase; butyrylcholinesterasa; Acetylcholinesterase; paraoxon; Organophosphorus Compounds; oximy; In Vitro Techniques; Paraoxon; techniky in vitro; lidé; organofosforové sloučeniny; Enzyme Reactivators; Financing, Organized; Oximes; acetylcholinesterasa; cholinesterasové inhibitory; Cholinesterase Inhibitors; enzymové reaktivátory; Humans